2022
DOI: 10.1093/jme/tjac022
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Identification of Cimex hemipterus Fabricius, 1803 (Hemiptera: Cimicidae) and First Report of C. lectularius Linnaeus, 1758, in Madagascar

Abstract: Bed bugs are hematophagous insects with a long history of presence in human communities. Over the last three decades, infestations by bed bugs in human dwellings have drastically increased, leading to a rise in bed bug concerns. This study was conducted in May 2019 in the Miarinarivo district of Madagascar. Eight locations with suspected infestations were inspected. Of these, five locations were found with active bed bug infestations. Overall, 23 (19 adults and four nymphs) specimens with numbers per apartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In Africa, bed bug infestations have been poorly documented over the past two decades. Cimex hemipterus was considered the most prevalent species, while C. lectularius was restricted to some countries in central and southern Africa such as Nigeria, Sierra Leone, Tanzania, and Madagascar ( Jupp et al, 1978 , Newberry and Jansen, 1986 , Gbakima et al, 2002 , Emmanuel et al, 2014 , Akhoundi et al, 2022 ). Furthermore, the accurate diagnosis of these species is crucial for designing effective control programs involving insecticide selection and the type of monitoring system used.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, bed bug infestations have been poorly documented over the past two decades. Cimex hemipterus was considered the most prevalent species, while C. lectularius was restricted to some countries in central and southern Africa such as Nigeria, Sierra Leone, Tanzania, and Madagascar ( Jupp et al, 1978 , Newberry and Jansen, 1986 , Gbakima et al, 2002 , Emmanuel et al, 2014 , Akhoundi et al, 2022 ). Furthermore, the accurate diagnosis of these species is crucial for designing effective control programs involving insecticide selection and the type of monitoring system used.…”
Section: Discussionmentioning
confidence: 99%
“…Since all previous studies in Iraq have merely relied on traditional methods for bed bugs' identification, it is necessary to employ molecular identification along with morphological identification to distinguish between the two similar species of bed bugs. Numerous studies have indicated that it is possible to achieve high accu-253 http://jad.tums.ac.ir Published Online: Sep 30, 2023 racy in distinguishing between the two species of bed bugs by relying on molecular identification and morphological identification (28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Besides tropical regions, C. hemipterus has recently expanded to other temperate zones in the Middle East, North Australia, the United States, Russia, Sweden, Italy, and France [6][7][8][9][10][11][12]. Similarly, C. lectularius has lately been reported from Madagascar [13].…”
Section: Introductionmentioning
confidence: 99%